Performance evaluation at different process parameters of an innovative prototype of biomass gasification system aimed to hydrogen production. (15th December 2016) - Pallozzi, V.; Di Carlo, A.; Bocci, E.; Villarini, M.; Foscolo, P.U.; Carlini, M.
Highlights: An innovative pure H2 production system from biomass gasification was investigated. Hot gas cleaning to remove tar and particulate, catalytic foams for water gas shift. Steam to biomass (1.0–2.0) and water gas shift operating conditions were varied. The results showed that chemical efficiency, HHV based, varies between 49% and 55%. Abstract: Gasification is currently considered one of the most effective technologies to produce power and hydrogen from biomass and the scope of this work is to determine performances of such an energy system in terms of production of pure hydrogen. The overall plant has been simulated by means of ChemCAD® software. It is composed of a dual fluidized bed biomass gasifier with Catalytic Filter candles (CF), innovatively integrated within the gasification reactor, Water Gas Shift reactor (WGS), equipped with a desulphurization reactor (DeS), and Pressure Swing Adsorber system (PSA), coupled with a micro gas-turbine system (mGT) as an auxiliary power generator aimed to supply inner needs of electricity. Research and pilot scale tests on gasifier, CF, WGS reactor and PSA unit allowed to validate the model. The components have been integrated in a relatively small size and innovative plant (1 MWth as biomass input). This integration entails highly pure H2 and major efficiency. The model allowed a sensitivity analysis of basic parameters as WGS temperature, residence time and steam to biomass ratio (SB). Important results have been generated reaching a maximum hydrogen yield of 75.2 gH2 /kgbio and a maximum efficiency, HHV based, of 55.1%. Optimal compromise of results was obtained with SB equal to 2, WGS reactor temperature at 300 °C and residence time at 0.8 s. Finally, even the chance to generate hydrogen without consumption of auxiliary fuel (by exploiting off gas and waste heat recovery) has been investigated.